PENGARUH PENERAPAN MODEL PEMBELAJARAN Teams-Games-Tournaments (TGT) BERBANTUAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X DI SMA NEGERI 1 KEPULAUAN SULA - Saidah Daeng Hanafi; Taslim D Nur; Arini Zohratun Nashicah (UNIVERSITAS KHAIRUN, 2022)
The era of the industrial revolution 4.0, data-based, technology and humanist education that contains various media as learning support becomes more effective to improve mindsets, interest in learning, attract students' attention and achieve the goals or objectives of the learning process carried out. The purpose of this study was to determine the effect of the application of the Teams-Games-Tournaments (TGT) learning model with video-assisted learning on critical thinking skills in class X students at SMA Negeri 1 Sula Islands. This research is a quasi-experimental research (Quasy Experiment). The sample of this study consisted of two classes, namely class X-A as the experimental class, X-B as the control class with 72 students. The instrument used is a test to measure cognitive learning outcomes. Data analysis used the SPSS-assisted normality and homogeneity test, while the hypothesis test and relationship test used the Anacova test. The results showed that there was an effect of implementing the Teams-Games-Tournaments (TGT) learning model on the critical thinking skills of Class X students at SMA Negeri 1 Sula Islands with a significant level of 0.009 while the average value of post-test critical thinking skills in the experimental class was 67. ,13% and the control class is 63.73%.